Efectos tóxicos y radiactivos del uranio - Sánchez Ocampo, Alfonso; Jiménez Reyes, Melania; Torres Pérez, Juan; López Castañares, Rafael; Olea Cardoso, Óscar (CIENCIA ergo-sum; Vol. 5 Núm. 3 (1998): CIENCIA ergo-sum (noviembre 1998-febrero 1999), 2017)
-